Inner Damping of Water in Conduit of Hydraulic Power Plant - Himr, Daniel; Habán, Vladimír; Štefan, David (MDPI, 2021)
The operation of any hydraulic power plant is accompanied by pressure pulsations that are caused by vortex rope under the runner, rotor–stator interaction and various transitions during changes in operating conditions or start-ups and shut-downs. Water in the conduit undergoes volumetric changes due to these pulsations. Compression and expansion of the water are among the mechanisms by which energy is dissipated in the system, and this corresponds to the second viscosity of water. The better our knowledge of energy dissipation, the greater the possibility of a safer and more economic operation of the hydraulic power plant. This paper focuses on the determination of the second viscosity of water in a conduit. The mathematical apparatus, which is described in the article, is applied to data obtained during commissioning tests in a water storage power plant. The second viscosity is determined using measurements of pressure pulsations in the conduit induced with a ball valve. The result shows a dependency of second viscosity on the frequency of pulsations.

The operation of any hydraulic power plant is accompanied by pressure pulsations that are caused by vortex rope under the runner, rotor–stator interaction and various transitions during changes in operating conditions or start-ups and shut-downs. Water in the conduit undergoes volumetric changes due to these pulsations. Compression and expansion of the water are among the mechanisms by which energy is dissipated in the system, and this corresponds to the second viscosity of water. The better our knowledge of energy dissipation, the greater the possibility of a safer and more economic operation of the hydraulic power plant. This paper focuses on the determination of the second viscosity of water in a conduit. The mathematical apparatus, which is described in the article, is applied to data obtained during commissioning tests in a water storage power plant. The second viscosity is determined using measurements of pressure pulsations in the conduit induced with a ball valve. The result shows a dependency of second viscosity on the frequency of pulsations.
Inner Damping of Water in Conduit of Hydraulic Power Plant
Keywords: second viscosity; bulk viscosity; measurement; hydraulic power plant; conduit; pressure pulsations; dissipation; damping; second viscosity; bulk viscosity; measurement; hydraulic power plant; conduit; pressure pulsations; dissipation; damping